Ensembl 2020. Issue Volume 48:Issue D1(2020) (6th November 2019) - Yates, Andrew D; Achuthan, Premanand; Akanni, Wasiu; Allen, James; Allen, Jamie; Alvarez-Jarreta, Jorge; Amode, M Ridwan; Armean, Irina M; Azov, Andrey G; Bennett, Ruth; Bhai, Jyothish; Billis, Konstantinos; et al.
Abstract: The Ensembl (https://www.ensembl.org ) is a system for generating and distributing genome annotation such as genes, variation, regulation and comparative genomics across the vertebrate subphylum and key model organisms. The Ensembl annotation pipeline is capable of integrating experimental and reference data from multiple providers into a single integrated resource. Here, we present 94 newly annotated and re-annotated genomes, bringing the total number of genomes offered by Ensembl to 227. This represents the single largest expansion of the resource since its inception. We also detail our continued efforts to improve human annotation, developments in our epigenome analysis and display, a new tool for imputing causal genes from genome-wide association studies and visualisation of variation within a 3D protein model. Finally, we present information on our new website. Both software and data are made available without restriction via our website, online tools platform and programmatic interfaces (available under an Apache 2.0 license) and data updates made available four times a year.